2019
DOI: 10.4049/jimmunol.1900113
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Animal Model of Emphysema Induced by Anti-Elastin Autoimmunity

Abstract: Loss of immune tolerance to self-antigens can promote chronic inflammation and disrupt the normal function of multiple organs, including the lungs. Degradation of elastin, a highly insoluble protein and a significant component of the lung structural matrix, generates proinflammatory molecules. Elastin fragments (EFs) have been detected in the serum of smokers with emphysema, and elastin-specific T cells have also been detected in the peripheral blood of smokers with emphysema. However, an animal model that cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…These models may be more relevant for the initial assessment of alveolar damage mechanisms. Recently, Gu et al [178] demonstrated the use of a murine model of anti-elastin autoimmunity resulting in emphysema that could be used to examine the role of immune tolerance in diseases, such as COPD, and enhance the clinical relevance of elastase-based models.…”
Section: Elastase Instillationmentioning
confidence: 99%
“…These models may be more relevant for the initial assessment of alveolar damage mechanisms. Recently, Gu et al [178] demonstrated the use of a murine model of anti-elastin autoimmunity resulting in emphysema that could be used to examine the role of immune tolerance in diseases, such as COPD, and enhance the clinical relevance of elastase-based models.…”
Section: Elastase Instillationmentioning
confidence: 99%